Analysis of the Use of Digital Financial System (E-Wallet) Financial Management of Farmers in Kota Pari Village - Maya Syaula; Fachrid Wadly (International Journal of Society and Law, 2024)
Financial technology (fintech) has experienced rapid development in recent years, one of the innovations is electronic wallets (e-wallets). E-wallets offer convenience in conducting financial transactions, including income and expense management. In Kota Pari Village, the majority of the population works as farmers. However, the adoption of fintech technology among farmers is still relatively low. This study aims to analyze the extent to which e-wallets are used by farmers in managing their income and expenses and identify the factors that affect their use. This research is expected to provide a comprehensive overview of the use of e-wallets by farmers in Kota Pari Village. The results of this research are expected to be the basis for the development of programs that support the improvement of financial literacy and the use of financial technology in the agricultural sector.